2018
DOI: 10.1016/j.celrep.2017.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Activity State, Axonal Projection, and Position Define the Transcriptional Identity of Individual Neocortical Projection Neurons

Abstract: SUMMARY Single-cell RNA sequencing has generated catalogs of transcriptionally defined neuronal subtypes of the brain. However, the cellular processes that contribute to neuronal subtype specification and transcriptional heterogeneity remain unclear. By comparing the gene expression profiles of single layer 6 corticothalamic neurons in somatosensory cortex, we show that transcriptional subtypes primarily reflect axonal projection pattern, laminar position within the cortex, and neuronal activity state. Pseudot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 59 publications
(95 reference statements)
7
97
0
Order By: Relevance
“…To obtain a detailed transcriptional profile of single RPCs over the course of retinal neurogenesis, we first performed single cell RNA-sequencing on FACS-isolated Chx10-GFP + mouse RPCs (Rowan and Cepko, 2004), using an adapted Smart-Seq2 protocol (Chevee et al, 2018) at embryonic (E) days 14 and 18, and postnatal (P) day 2, which correspond to early, intermediate and late stages of retinal neurogenesis, respectively ( Figure 1B). Analysis of 780 individual RPCs profiled to a depth of ~750,000 aligned fragments per cell (mean 762,726; sd 291,612.5; Figure S1A-D) revealed that these cells resolved into three major clusters that express canonical RPC markers (e.g.…”
Section: Examination Of Retinal Progenitor Cell Heterogeneity Via Smamentioning
confidence: 99%
“…To obtain a detailed transcriptional profile of single RPCs over the course of retinal neurogenesis, we first performed single cell RNA-sequencing on FACS-isolated Chx10-GFP + mouse RPCs (Rowan and Cepko, 2004), using an adapted Smart-Seq2 protocol (Chevee et al, 2018) at embryonic (E) days 14 and 18, and postnatal (P) day 2, which correspond to early, intermediate and late stages of retinal neurogenesis, respectively ( Figure 1B). Analysis of 780 individual RPCs profiled to a depth of ~750,000 aligned fragments per cell (mean 762,726; sd 291,612.5; Figure S1A-D) revealed that these cells resolved into three major clusters that express canonical RPC markers (e.g.…”
Section: Examination Of Retinal Progenitor Cell Heterogeneity Via Smamentioning
confidence: 99%
“…In contrast, responses of α9α10 nAChRs from rat, 226 chicken and frog exhibited differential modulation by extracellular Ca 2+ . As previously reported for 227 the rat α9α10 receptor, responses to ACh were potentiated and blocked by extracellular Ca 2+ ( Calcium permeation through nAChRs holds great functional significance for the activation of calcium 234 dependent conductances and intracellular signalling pathways (14). Receptors containing the α7 235 subunit have high calcium permeability (40) whereas receptors containing α4β2 subunits have a 236 lower contribution of calcium to the total current (28,41).…”
Section: Divergence Of Biophysical Properties Differentiates Neuronalmentioning
confidence: 67%
“…With the exception of some fish species 318 that acquired α11, β1.2 and β5 subunits, for which no expression or functional data has yet been 319 reported (10), and the loss of the α7-like α8 subunits in mammals, the complement of original 320 vertebrate nAChR subunits has been remarkably conserved. Moreover, nAChRs are unique in that 321 subgroups of the family have distinct roles in synaptic transmission in non-overlapping domains, 322 either in the nervous system, inner ear hair cells or the neuromuscular junction (13,14,18). In this 323 work, we performed in-depth analyses of coding sequence molecular evolution, subunit co-324 expression patterns and comparative functional properties of neuronal and hair cell receptors to 325 explore the potential impact of these segregation of nAChRs subgroups on their respective 326 evolutionary histories.…”
Section: Comparative Functional Analysis Of Neuronal and Hair Cell Namentioning
confidence: 99%
See 2 more Smart Citations